Chemical modification of enveloped viruses for biomedical applications. Issue 11 (8th October 2018) - Ratnatilaka Na Bhuket, Pahweenvaj; Luckanagul, Jittima Amie; Rojsitthisak, Pornchai; Wang, Qian
Abstract : Chemistry enables scientists to use enveloped viruses in several biomedical applications including bio-imaging, drug delivery and vaccine development. Abstract : The unique characteristics of enveloped viruses including nanometer size, consistent morphology, narrow size distribution, versatile functionality and biocompatibility have attracted attention from scientists to develop enveloped viruses for biomedical applications. The biomedical applications of the viral-based nanoparticles include vaccine development, imaging and targeted drug delivery. The modification of the structural elements of enveloped viruses is necessary for the desired functions. Here, we review the chemical approaches that have been utilized to develop bionanomaterials based on enveloped viruses for biomedical applications. We first provide an overview of the structures of enveloped viruses which are composed of nucleic acids, structural and functional proteins, glycan residues and lipid envelope. The methods for modification, including direct conjugation, metabolic incorporation of functional groups and peptide tag insertion, are described based on the biomolecular types of viral components. Layer-by-layer technology is also included in this review to illustrate the non-covalent modification of enveloped viruses. Then, we further elaborate the applications of chemically-modified enveloped viruses, virus-like particles and viral subcomponents in biomedical research.